Longitudinal Surveillance of Invasive Mosquitoes at Points of Entry in Northeastern Italy - Sara Manzi; Martina Micocci; Luca Tassoni; Stefano Vettore; Davide Bonetto; Simone Martini; Francesco Gradoni; Federica Toniolo; Giulia Iandiorio; Lidia Iustina Danca; Giulia Chiarello; Patrizia Visentin; et al. (Tropical Medicine and Infectious Disease, 2026)
Aedes invasive mosquito (AIM) species are expanding worldwide, increasing the risk of arbovirus introduction and transmission. Points of Entry (PoEs), including airports and seaports, represent critical gateways for the introduction and spread of invasive vectors through international passenger and cargo traffic. This study evaluated the AIM long-term dynamics at three major PoEs (Treviso Airport, Venice Airport, and Venice Port) in northeastern Italy (Veneto region) between 2018 and 2024 through an integrated entomological surveillance programme designed to collect AIMs (adults and eggs) throughout the seasonal activity (June–October). Mosquitoes were identified morphologically and, where required, by molecular analyses. Aedes albopictus was the dominant AIM throughout the study period (eggs N = 96,192, adults N = 14,231), being detected at all three study sites and showing consistent interannual and seasonal dynamics, with peak abundance during summer despite routine vector control interventions. Aedes koreicus was detected at two of the three study sites, namely Venice and Treviso airports (eggs N = 1, adults N = 3). Phylogenetic analyses based on COI indicated that these specimens belonged to a distinct European lineage, revealing genetic diversity among European populations of Ae. koreicus. No evidence of newly established AIMs was found during the surveillance period. These findings highlight the importance of long-term surveillance at PoEs for the early detection of AIMs, monitoring temporal changes in established vector populations, and supporting integrated control and surveillance strategies to reduce the risk of vector establishment and mosquito-borne disease transmission.